Advances in Human Factors and Ergonomics in Healthcare and Medical Devices : proceedings of the AHFE 2018 International Conference on Human Factors and Ergonomics in Healthcare and Medical Devices, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: proceedings of the AHFE 2018 International Conference on Human Factors and Ergonomics in Healthcare and Medical Devices, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. (2018) - Unknown
No abstract available